Mothering Through Mental Illness: Exploring the Experiences of Motherhood for Criminally Involved Women on Mental Health Probation - Mulvey, Philip (Crime & delinquency, 2022)
As the number of criminally involved women has increased substantially over several decades, the prevalence of mothers impacted by criminal justice involvement has also increased. The current paper seeks to examine a specific subset of these criminally involved mothers?those with significant and long-term mental illness. This study explores how these women describe their experiences mothering through semistructured qualitative interviews with 48 women on a specialty mental health caseload in Maricopa County, Arizona. Using an inductive approach inspired by grounded theory to analyze the narrative accounts of criminally involved women with mental illness, the maternal identities of these women are placed at the forefront of the discussion, with an emphasis on examining their experiences beyond motherhood?s influence on desistance.